Metallic Equivalent of Aircraft Landing Gear Using Composite Materials - Kotze, Marius Hugo (University of the Witwatersrand, Johannesburg, 2024)
There are two types of Light Sport Aircraft landing gear configuration. The taildragger and tricycle arrangement where the difference is specified by the position of the main landing gear. Shipment delay of the current Aluminium 7075 T6 landing gear has caused further delays in the manufacturing of the BushCat Light Sport Aircraft. Thus, a composite alternative was required which could be manufactured locally. The objective was to determine which locally available material was best suited as an alternative to the current Aluminium 7075 T6 design. This included estimation of the correct design loads acting on the BushCat aircraft main landing gear and to specify a composite alternative that could withstand these calculated design application loads. The loads that were used would be obtained from the ASTM F2245-14 regulations and EASA CS-23 amendments. The loads were validated by means of Finite Element Analysis and analytical calculations. Drop tests were also conducted by the company and image processing was used to compare the calculated deformations to the FEA results. This was used to validate the load and constraint applications in Ansys 2023 R2 software. The composite materials used for analysis were unidirectional epoxy e-glass wet layup and prepregs fibres. A coupon study was conducted on Aluminium 7075 T6 alloy and [0/90/90/0], [0/45/45/0], [0/90/45/0] layered unidirectional epoxy e-glass wet layup and prepreg coupons loaded under tension, compression, bending and torsion. The FEA results were validated using analytical calculations obtained from the Classical Lamination Theory. It was concluded that the unidirectional epoxy e-glass prepreg coupons were best suited as an alternative as better results in withstanding the applied load applications were obtained. The prepreg fibres also contained a lower void content in comparison to the wet layup fibres, thus increasing the fatigue life of the composite laminate as well as reducing the moisture absorption. The final composite landing gear was analysed using the Puck-failure criterion and it was found that after analysis and modifications were conducted, the newly designed composite landing gear could withstand the applied loads during limit load and ultimate load conditions without any fibre or inter-fibre failure in the strut of the landing gear. It was found that, failure had occurred in one of the fibre plies near the bolted regions of the axle section during ultimate (emergency) landing conditions and was thus concluded that the composite landing gear should still be inspected when attempting emergency landing at higher load conditions at an aircraft maximum take-off weight of 600 kg. The final composite landing gear design after modifications was 4.613 kg heavier than the Aluminium 7075 T6 landing gear. With regards to manufacturing the final composite landing gear a vacuum bagging process should be followed where the final vacuum bagging assembly containing the composite layup of the landing gear should be placed inside an oven or autoclave to start the curing process. Once the composite landing gear is cured, it could be machined into its final shape were non-destructive techniques such as ultrasound of thermography should be used to inspect the final composite landing gear for any air of volatile compounds withing the laminate. Static and dynamic destructive testing should also be used to validate if the final composite landing gear can withstand all landing conditions aircraft maximum weight without any fibre failure or delamination occurring.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Metallic Equivalent; Aircraft Landing Gear; omposite Materials; SDG-9: Industry, innovation and infrastructure